Influence of Supervisors’ Fairness on Work Climate, Job Satisfaction, Task Performance, and Helping Behavior of Health Workers During COVID-19 Outbreak - Wang, WenXin; Ahoto, Ahotovi T. (Frontiers in Psychology, 2022)
The role of supervisors in health delivery was actively exhibited during the initial stages of the covid-19 outbreak. Nonetheless, the number of deaths and hospitalization was alarming health workers were actively working throughout the time. This study explores the role of supervisors' fairness in creating a work climate and job satisfaction that promote workers' task performance and helping behaviors. The researchers adopted a quantitative method with a questionnaire used for data collection. SPSS and AMOS were used for data analysis, statistical models of correlation and hierarchical regression were used to examine relationships among the variables. The study established that supervisors’ fairness has positive effect on work climate, job satisfaction, task performance and helping behavior of health workers. Work climate has positive effects of task performance and helping behaviors, while job satisfaction also have positive effects on employees task performance and helping behavior. The researchers recommended the need for supervisors to exhibited fairness to worker at all time and create the room for workers to appeal their decision to avoid the feeling of supervisors’ biasness.